The Relationship between the TCF7L2 rs7903146 Gene Polymorphism and Anthropometric Parameters and Muscle Mass among Patients with Type 2 Diabetes Mellitus at Puskesmas Waruroyom, Cirebon - Muhammad Ajmalunnas; Yuni Susanti Pratiwi; Tiar Masykuroh Pratamawati; Donny Nauphar; Edhyana Sahiratmadja; Leonardo Lubis (Masters Program in Public Health, 2026)
Background: Polymorphism of the TCF7L2 gene (rs7903146) is involved in glucose homeostasis and has been strongly associated with type 2 diabetes mellitus (T2DM). However, its relationship with anthropometric characteristics, particularly by glycemic control status, remains unclear. Subjects and Method: This cross-sectional study included 75 patients with type 2 diabetes mellitus (T2DM) in the working area of Puskesmas Waruroyom, Cirebon. The target population comprised all registered T2DM patients, and total sampling was applied through screening. Subjects were classified into controlled (n = 37; 49.3%) and uncontrolled (n = 38; 50.7%) groups based on glycemic status. TCF7L2 rs7903146 genotypes (CC, CT, TT) were identified, and anthropometric parameters (height, body weight, BMI, waist circumference, and muscle mass) were analyzed using chi-square or Fisher’s exact tests, with additional analyses for continuous variables. Results: The most frequent genotype was CT (69.3%), followed by TT (25.3%) and CC (5.3%). No significant differences were observed in anthropometric parameters across TCF7L2 rs7903146 genotypes in both controlled and uncontrolled groups, including BMI (p= 0.580 and p= 0.830), waist circumference (p= 1.000 and p= 0.760), and muscle mass (p= 1.000 and p= 0.420), respectively. Conclusion: The TCF7L2 rs7903146 polymorphism was not associated with anthropometric profiles among patients with T2DM, regardless of glycemic control status. This suggests that the influence of TCF7L2 is more strongly related to metabolic regulation through insulin signaling pathways rather than to determinants of body composition.